The relationship of knowledge management practice on is outsourcing success in telecomunication sector - Fajrillah, Asti Amalia Nur (2014)
Information System (IS) outsourcing can be defined as turning over part or all of an organization’s IS functions to external service provider, to acquire economic, technological, and strategic advantage. In regards on cost-effective access to specialized computing power or system development skill, outsourcing has become an important option for organization around the world. But, it is not easy to achieve goals in IS outsourcing; there are factors that need to take to achieved the overall organizational advantage obtained from IS outsourcing so that one organization can categorized it’s IS outsourcing conducted as success. In particular, Knowledge Management (KM) practices defined as the process of knowledge management called knowledge cycle which includes the activities of creation, sharing and application of knowledge. In many organizations, KM seen as a key factor to gain and sustain competitive advantage. Furthermore, knowledge seen as crucial factors in IS outsourcing success. This study aims to examine the relationship of knowledge management practices (knowledge creation, knowledge sharing, and knowledge application) on IS outsourcing success through IS outsourcing determinants (communication quality and partnership quality). This study used quantitative research methodology by participating 66 projects managers in Indonesian Telecommunication sector. The results revealed knowledge application as the last phase in knowledge management practices have significantly affect IS outsourcing success through communication quality and partnership quality as IS outsourcing determinants. Finally, providing knowledge management practices model can be used as guidance by those organizations which conduct IS outsourcing to achieve IS outsourcing success and to obtain the overall organizational advantage from IS outsourcing.